Tertiary lymphoid structures favor outcome in resected esophageal squamous cell carcinoma - Rutao Li; Xing Huang; Wenmin Yang; Jifan Wang; Yingkuan Liang; Te Zhang; Qixing Mao; Wenjie Xia; Lin Xu; Xinyu Xu; Gaochao Dong; Feng Jiang (Wiley, 2022)
Abstract Tertiary lymphoid structures (TLSs) are considered to have a good prognosis in multiple solid tumors. However, the prognostic value of TLS in esophageal squamous cell carcinoma (ESCC) is unknown. In this study, we retrospectively enrolled 185 ESCC patients who underwent surgical resection. Hematoxylin and eosin staining was performed to investigate the presence, the abundance, the maturation, and the location of TLSs. We explored the cellular composition of TLSs using traditional immunohistochemistry in serial sections. The prognostic value of TLSs was investigated by univariate and multivariate analyses. A nomogram was constructed to predict the prognosis. TLS‐positive tumors were infiltrated with more CD45+ leukocytes, CD20+ B cells, CD4+ and CD8+ T cells, and CD11c+ dendritic cells（DCs） compared with negative tumors. Kaplan-Meier curves showed that the presence and the abundance of TLSs were associated with longer disease‐free survival (DFS) (p = 0.0130) and overall survival (OS) (p = 0.0164). In addition, patients with tumors containing more CD20+ B cell infiltration had longer DFS (p = 0.0105) and OS (p = 0.0341). Multivariate analyses demonstrated that the presence of TLSs was an independent prognostic factor for DFS (hazard ratio [HR] = 0.384, p < 0.001) and OS (HR = 0.293, p < 0.001). The nomogram that integrated the tumor stage, histologic grade, and TLS presence had higher prognostic accuracy. Our study suggests that ESCC‐related TLSs can be used as a new biomarker for the prognosis of ESCC patients, and further understanding of their formation and mechanism of induction can provide a possible direction and target for immunotherapy of ESCC.